Antihypoxant Activity of Low Molecular Weight Fraction Bovine Blood Cryohemolysate at Different Stages of Ontogenesis - Gulevsky, Oleksandr K.; Schenyavsky, Ivan I. (Problems of Cryobiology and Cryomedicine, 2017)
Antihypoxant activity of low-molecular weight (below 5 kDa) fraction, obtained by ultrafiltration from cryohemolysate of umbilical/placental bovine and peripheral blood of 3-month-old calves and 4–5-year-old cows was studied. It was shown that injections of the fraction derived from bovine cord blood and the one of 3-month-old calves unlike low molecular fraction of bovine blood significantly increased the survival time of mice in confined space and inhibited the accumulation of malon dialdehyde and lipid hydroperoxides in brain tissue at experimental confined space hypoxia. The effect after a preliminary 5-days course of injections of these drugs was the most pronounced. Thus, low molecular weight fraction below 5 kDa of blood at the early stages of ontogenesis had lower antihypoxant activity in animals with age. The obtained results testify to the fact that cryogenic technologies enable to use bovine cord blood as a raw material source for the production of pharmaceuticals with an antihypoxant action. Probl Cryobiol Cryomed 2017; 27(1): 41–50